2013
DOI: 10.1016/j.cmet.2013.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Mediates the Metabolic Effects of FGF21 on Glucose Homeostasis and Insulin Sensitivity in Mice

Abstract: Fibroblast growth factor 21 (FGF21) is a metabolic hormone with pleiotropic effects on regulating glucose and lipid homeostasis and insulin sensitivity. However, the mechanisms underlying the metabolic actions of FGF21 remain unknown. Here we show that the insulin-sensitizing adipokine adiponectin is a downstream effector of FGF21. Treatments with FGF21 enhanced both expression and secretion of adiponectin in adipocytes, thereby increasing serum levels of adiponectin in mice. Adiponectin knockout mice were ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

33
500
10
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 577 publications
(564 citation statements)
references
References 50 publications
(87 reference statements)
33
500
10
1
Order By: Relevance
“…Therefore, OSM seems to be a candidate for a powerful therapeutic agent without unfavourable side effects in the treatment of obesity-related metabolic diseases. Recently, it has also been reported that the metabolic effects of FGF21 are mediated by adiponectin (the so-called 'FGF21- [27,28]. In the present study, treatment with OSM did not induce an increase in serum adiponectin levels, suggesting that OSM exerts its metabolic effects independent of adiponectin.…”
Section: Discussionsupporting
confidence: 47%
“…Therefore, OSM seems to be a candidate for a powerful therapeutic agent without unfavourable side effects in the treatment of obesity-related metabolic diseases. Recently, it has also been reported that the metabolic effects of FGF21 are mediated by adiponectin (the so-called 'FGF21- [27,28]. In the present study, treatment with OSM did not induce an increase in serum adiponectin levels, suggesting that OSM exerts its metabolic effects independent of adiponectin.…”
Section: Discussionsupporting
confidence: 47%
“…Mice with combined apolipoprotein E and FGF21 deficiency had worsened hyperlipidemia, increased expressions of both local and systemic proinflammatory chemokines and cytokines, with resultant acceleration of aortic plaque formation,28 compared with mice with apolipoprotein E deficiency only. Although these antiatherosclerotic properties of FGF21 could be explained by adiponectin, which had been shown to mediate the effects of FGF21 on glucose homeostasis and insulin sensitivity in mice,29 FGF21 could also ameliorate atherosclerosis independent of adiponectin, through suppression of cholesterol biosynthesis by directly inhibiting sterol regulatory element‐binding protein‐2 28. In another study using FGF21 knockout mice and cultured rat neonatal cardiomyocytes, FGF21 deficiency enhanced isoproterenol induced cardiac hypertrophy, increased cardiac expressions of proinflammatory genes, as well as markers of cardiac hypertrophy and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Recent data report the involvement of a cross-talk between adiponectin and fibroblast growth factor 21 (FGF21) in the insulin-sensitizing effect of adiponectin. FGF21, a metabolic hormone that regulates glucose and lipid homeostasis and insulin sensitivity [39], enhances adiponectin secretion by adipocytes and increases circulating adiponectin in mice [40,41]. Interestingly, FGF21 decreases accumulation of ceramides in obese animals in an adiponectin-dependent fashion.…”
Section: Introductionmentioning
confidence: 99%